La metamorfosis de la política exterior de Recep Tayyip Erdoğan: de un populismo internacional a uno transnacional-limitado - Colalongo, Rodolfo E.; Rayran-Cortés, Manuel Alejandro (El Colegio de México A.C., 2023)
The intention of this paper is to highlight the main points of connection between populism and international relations, taking as a case study Turkish foreign policy during the government of Tayyip Erdoğan (2003-2020). The theory that accounts for populism as a factor of emancipation are connected with foreign policy as a public policy that responds to intermestic demands. Then, some discursive fragments of the president’s speeches are analyzed, in the understanding that words are transformed into political actions, seeking to interweave populism as a constitutive framework of his speeches, foreign policy as his field of action, and international relations as his context of production, in order to understand the kind of foreign policy the Erdoğan government carried out during that period.